The Effect of Acute and Chronic Noise Stress Exposure on some Physiological and Immunological Parameters in Male and Female Adult Mice - A. A. Al-Shammary, Zainab; A.K., Sally; Sameer Sabti, Zainab; Jouda, Jamela; A. Hameid, Sabah (Al-Nahrain Journal of Science, 2024)
Noise, the most commonly encountered stressor in our daily lives, affects the body in different ways depending on its frequency, intensity, and duration. Thus, this study aimed to demonstrate the effect of noise stress exposure in different durations on the immunological status of female and male adult mice. Sixty female and male adult mice (Balb / C) were used in this. Fifty mice were exposed to noise stress at 90 degrees for four hours per day, and 10 mice (5 males and 5 females) were left without exposure to stress which was used as a control group. Exposure stress mice were divided into five groups (n = 10, 5 males and 5 females); Group1 was exposed to noise stress for only 1 day, Group2 for 8 days, Group3 for 14 days, Group4 for 21 days, and Group5 for 30 days. The blood sample was collected and used for immunoglobulins, glucocorticoids and WBCs indices tests. Results showed that there was a highly significant increase in glucocorticoids for all periods after noise exposure. WBC count, the level of IgG and IgM were highly significant in mice that were exposed to noise stress during 1, 8, 14, and 21 days, while there was no significant difference in the 28-days stress group compared to control. In conclusion, the levels of immunoglobulins levels after 28 day of noise stress exposure could completely differ from the short-term exposure.